2016
DOI: 10.1080/09637486.2016.1181156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on body weight and body-mass index: a systematic review and meta-analysis of randomized, controlled trials

Abstract: Consuming probiotics could reduce body weight and BMI, with a potentially greater effect when multiple species of probiotics were consumed, the duration of intervention was ≥8 weeks, or the objects were overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 49 publications
5
73
0
4
Order By: Relevance
“…In accordance with our findings, previous reviews have found probiotics to reduce body weight in adults, and the reported effect sizes were small (19,50). However, to the best of our knowledge, this is the first of recent reviews including only overweight/obese adults or populations.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 91%
“…In accordance with our findings, previous reviews have found probiotics to reduce body weight in adults, and the reported effect sizes were small (19,50). However, to the best of our knowledge, this is the first of recent reviews including only overweight/obese adults or populations.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 91%
“…For instance, treatment with natural probiotics has been shown to significantly increase HDL only in patients with a baseline BMI ≥ 29 kg/m 2 [153] or significantly reduce BMI only in participants with a baseline BMI ≥ 25 kg/m 2 [154]. Regarding flavanol-containing products, a previous meta-analysis of the effects of black tea on blood cholesterol failed to detect differences in the modulation of cholesterol levels between individuals with normal weight or overweight and obese phenotype, but the results of this meta-analysis were estimated using a very small number of trials per subgroup (4 and 5, respectively) [141].…”
Section: Discussionmentioning
confidence: 99%
“…These reductions constitute between 5% and 10% of the WHO established limit values for overweight (BMI = 25.0–29.9 kg/m 2 ) and obesity (BMI ≥ 30.0 kg/m 2 ). Alternatively, intervention with probiotics [154] or nutraceuticals (e.g., lipoic acid) [164] shows a more modest but also significant reduction of BMI (approximately −0.5 kg/m 2 , ~2% change of the WHO values). On average, the size effect of the flavanol-containing products on BMI was smaller (−0.15 kg/m 2 , Table S3) but, notably, this effect may be enhanced in specific subpopulations (up to −0.91 kg/m 2 in studies conducted in European Mediterranean countries), more similar to other behavioral or dietary interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics can also enhance the immune system, improve the skin's function, enhance resistance against cedar pollen allergens, and decrease body pathogens, as well as protecting DNA, proteins and lipids from oxidative damage. They can also maintain an individual’s intestinal microbiota in subjects receiving antibiotic treatment [8,9,10,11]. In particular, it has been reported that gut probiotics play a major role in bidirectional communication between the gut and the brain [12,13].…”
Section: Introductionmentioning
confidence: 99%